Effect of stem cell conditional medium-loading adhesive hydrogel on TGF-β1-induced endometrial stromal cell fibrosis - Zhu, Yuan; Wang, Ting; Bao, Ming-Jie; Qu, Xiao-Hui; Li, Zeng-Ming (Frontiers in Bioengineering and Biotechnology, 2023)
Uterine adhesion (IUA) is a severe complication that results from uterine operations or uterine infections. Hysteroscopy is considered the gold standard for the diagnosis and treatment of uterine adhesions. Yet, this invasive procedure leads to re-adhesions after hysteroscopic treatment. Hydrogels loading functional additives (e.g., placental mesenchymal stem cells (PC-MSCs)) that can act as physical barriers and promote endometrium regeneration are a good solution. However, traditional hydrogels lack tissue adhesion which makes them unstable under a rapid turnover of the uterus, and PC-MSCs have biosafety risks when used as functional additives. In this study, we coupled an adhesive hydrogel with a PC-MSCs conditioned medium (CM) to form a hybrid of gel and functional additives (CM/Gel-MA). The results show that CM/Gel-MA enhances the activity of endometrial stromal cells (ESCs), promotes cell proliferation, and reduces the expression of α-SMA, collagen I, CTGF, E-cadherin, and IL-6, which helps to reduce the inflammatory response and inhibit fibrosis. We conclude that CM/Gel-MA can more potentially prevent IUA by combining the physical barriers from adhesive hydrogel and functional promotion from CM.